ガイコク キョウドウ ケンキュウ ホウコク ナンキョク プリッツ ワン デノ ニチ ゴウ カイヨウ セイブツ キョウドウ チョウサ 1992 - 渡辺, 研太郎; ワタナベ, ケンタロウ; 佐々木, 洋; ササキ, ヒロシ; 福地, 光男; フクチ, ミツオ; Watanabe, Kentaro; Sasaki, Hiroshi; Fukuchi, Mitsuo (1993)
P(論文) 平成3年度から3年計画で, 「南極海海洋環境変動と生物過程の研究」との研究課題の下にオーストラリアと共同観測が始められた。初年度はプリッツ湾を主とした海氷域および沿岸観測基地周辺における生物生産過程の解明を研究テーマとし, H. MARCHANT博士(オーストラリア南極局)との共同研究"The production and fate of biogenic particles in the Antarctic marine ecosystem"をオーストラリア南極観測船, オーロラ・オーストラリス(RSV AURORA AUSTRALIS)の第6航海(1992年1月9日から3月27日)で行った。本研究の目的は, (1)係留実験により, プリッツ湾海氷域での低次生産およびその生産物の沈降過程の経時変化を年間を通して観測し, (2)低次生産者群集を構成する各種群の寄与を調べることである。そのため, プリッツ湾海域に時間分画式セディメントトラップおよび現場クロロフィル記録計, 海流計を係留し, かつ採水, プランクトンネットによる採集, 培養実験を実施した。また, 南大洋における優占的な一次捕食者, ナンキョクオキアミの摂餌選択性に関する電気生理学的実験を行った。 A three-year research collaboration with biologists in the Australian Antarctic Division, on the variability in the Antarctic marine environment and its effects on the biological processes has started from the 1991/92 austral summer season. For the first year, a joint proposal of H. MARCHANT (Australian Antarctic Division) and M. FUKUCHI (National Institute of Polar Research) to investigate biological processes in the Prydz Bay and the coastal ice-covered areas, titled "The production and fate of biogenic particles in the Antarctic marine ecosystem" was submitted and carried out during the voyage 6 of the Australian Antarctic research ship, AURORA AUSTRALIS from January 9 to March 27,1992. Main objectives of this research were; 1) to investigate seasonal variations in the primary and secondary productions and sinking processes of the products throughout the year with moored instruments and 2) to estimate the contribution of different components to the production and sinking processes of lower trophic organisms. For these objectives, time-series sediment traps with an in-situ chlorophyll recorder and current meters were deployed and water collections, plankton-net samplings and incubation experiments were carried out in the Prydz Bay area. The feeding selectivity of the antarctic krill (Euphausia superba), a dominant primary consumer in the Southern Ocean, was preliminarily investigated with a simple electrophysiological method. departmental bulletin paper